Línea de postres libres de lactosa - Nieto García, Paola Alexandra (2018)
This project investigates the use of products without milk and derivatives for the preparation of lactose-free desserts. Currently the Ecuadorian market is unattended with products for lactose intolerant. Lactose-free products are few or very little known. This product is characterized by being handcrafted and mainly satisfying an abandoned sector. Knowing that this condition is not well recognized in Ecuador, although the symptoms of this disease are almost always present in a person's daily life, they are ignored. Vegetable milk is a good substitute for animal milk. The vegetable milk is prepared by hand using the grain or seed of any kind. These milks are rich in carbohydrates, lack cholesterol and growth hormones. These milks are beneficial for human consumption and will be used to make this line of lactose-free desserts. These desserts will be evaluated by professionals experts, who will help evaluate, correct and approve the desserts line. Contributing their knowledge and improving the quality and texture of the desserts. It will also be submitted to a focus group to evaluate the acceptance of these products in the future market. To finalized with the project, it will be developed a manual that will serve as a future reference guide to continue with the elaboration of these products. And change the gastronomic future of the country.